Efeito antimicrobiano, antioxidante, anti-inflamatório e gastroprotetor de nitro complexos de rutênio - Sasahara, Greyce Luri (2021)
Gastric lesions are related to multifactorial causes such as Helicobacter pylori infection, excessive consumption of non-steroidal anti-inflammatory drugs (NSAIDs), and ethanol. The inflammatory process and the production of reactive oxygen species (ROS) amplify tissue damage and hinder the healing process. Objective: To investigate the anti-inflammatory, antioxidant, antimicrobial, and gastroprotective effects of nitro ruthenium complex. To develop an analytical method (HPLC UV-Vis) to quantify and evaluate the behavior of the compound under different stress conditions. Methods and discussion: The antimicrobial activity of the compounds was evaluated for the minimal inhibitory concentrations (MIC) and minimal bactericidal concentrations (CBM) against Helicobacter pylori strain (ATCC 43504). The FOR0811C complex has MIC and CBM corresponding to 690 μM and 1390 μM, respectively. FOR0011F complex shows 40.6% inhibition of bacterial growth only at the highest concentration. RAW 264.7 cells stimulated with lipopolysaccharide (LPS) and treated with FOR0811C and FOR0011F (3 - 25 µM) were used to determine antioxidant and anti-inflammatory potential in vitro. Both compounds were prepared to suppress the production of reactive anions, being FOR0811C a superior antioxidant potential than FOR0011F compound, even when tested in smaller doses. The FOR0811C complex (6 - 25 µM), in all practices tested, was able to reduce mRNA expression for COX-2, IL1-β, as well as the production of cytokines TNF-α and IL-6 in RAW 264.7 cells, stimulated with LPS. In the second stage of the project, in vivo experiments were carried out with Swiss mice. The acute toxicity protocol administered FOR0811C (v.o.) at the maximum dose of 2000 mg/Kg. We observed the mice for 14 days; deaths or any changes in parameters: weight, water, and feed, were not found. Next, we evaluated the gastroprotective potential of the compound FOR0811C in indomethacin-induced gastric lesions and observed a reduction with the high concentration of the compound FOR0811C. FOR0811C (6 and 9 mg/kg) also promotes the reduction of ethanol-induced ulcers. Mice were pretreated with the compound FOR0811C (9 mg/kg) and then induced as gastric by ethanol for the antioxidant activity evaluation. The compound FOR0811C promoted increased enzymatic activity of catalase, superoxide dismutase enzyme, and glutathione peroxidase and reduced myeloperoxidase activity. Also observed a reduction in non-protein malondialdehyde levels. The gastroprotective effect of FOR0811C, in a gastric injury model induced by ethanol, was statistically inhibited for pretreatment with indomethacin (a cyclooxygenase inhibitor), glibenclamide (potassium channel blocker), or ODQ (soluble guanylate cyclase inhibitor). The chromatographic profile, calibration curve, quantification limit, detection limit, and behavior under different stress conditions of the FOR0811C complex were overcome by HPLC UV-Vis. Conclusion: The FOR0811C compound has antioxidant, antimicrobial, anti-inflammatory potential through the in vitro model of inflammation and an important antioxidant, anti-inflammatory, and gastroprotective potential in an in vivo model of gastric injury by ethanol. The gastroprotective mechanism of the FOR0811C nitro complex appears to be dependent on the prostaglandin pathway and the ATP-dependent cGMP/potassium channel pathway. The results allowed the development of the analytical method and evaluation of the pharmacological potential of nitro ruthenium complex.